Contemporary African American Literature : The Living Canon - Moody-Turner, Shirley; King, Lovalerie (Book collections on Project MUSE., 2013)
In this volume, the editors have compiled a collection of essays that offer access to contemporary Black fiction while addressing important issues in current African American literary studies. Scholars Houston Baker, Trudier Harris, Darryl Dickson-Carr, and Maryemma Graham join writers and younger scholars to explore the work of Toni Morrison, Edward P. Jones, Trey Ellis, Paul Beatty, Mat Johnson, Kyle Baker, Danzy Senna, Nikki Turner, and many others. The collection is bracketed by a foreword by novelist and graphic artist Mat Johnson, one of the most exciting and innovative contemporary African American writers, and an afterword by Alice Randall, author of the controversial parody The Wind Done Gone. Together, King and Moody-Turner make the case that diversity, innovation, and canon expansion are essential to maintaining the vitality of African American literary studies.